Chronic Hepatitis C-Related Cirrhosis Hospitalization Cost Analysis in Bulgaria - Dimitrova, Maria; Pavlov, Kaloyan; Mitov, Konstantin; Genov, Jordan; Petrova, Guenka Ivanova (Frontiers in Medicine, 2017)
Objective: HCV infection is a leading cause of chronic liver disease with long-term complications - extensive fibrosis, cirrhosis and hepatocellular carcinoma. The objective of this study is to perform cost analysis of therapy of patients with chronic HCV - related cirrhosis hospitalized in the University Hospital “Queen Joanna-ISUL” for 3-year period (2012-2014). Methods: It is a prospective, real life observational study of 297 patients with chronic HCV infection and cirrhosis monitored in the University Hospital “Queen Joanna-ISUL” for 3-year period. Data on demographic, clinical characteristics and healthcare resources utilization (hospitalizations, highly-specialized interventions, pharmacotherapy) was collected. Micro-costing approach was applied to evaluate the total direct medical costs. The points of view are that of the National Health Insurance Fund (NHIF), hospital and the patients. Collected cost data are from the NHIF and hospitals tariffs, patients, and from the positive dug list for medicines prices. Descriptive statistics, Chi-squared test, Kruskal-Wallis and Friedman tests were used for statistical processing. Results: 76% of patients were male. 93% were diagnosed in grade Child-Pugh A and B. 97% reported complications, and almost all developed esophageal varices. During the 3 years observational period patients did not change the critical clinical values for Child-Pugh status and therefore the group was considered as homogenous. 847 hospitalizations were recorded for 3 years period with average length of stay 17 days. The mortality rate of 6.90% was extremely high. The total direct medical costs for the observed cohort of patients for 3-year period accounted for 1 290 533 BGN (659 839 euro) with an average cost per patient 4577 BGN (2340 Euro). Statistically significant correlation was observed between the total cost per patient from the different payers` perspective and the Child-Pugh cirrhosis score. Conclusions: HCV-related cirrhosis is resource demanding and sets high direct medical costs as it is related with increased hospitalizations and complications acquiring additional treatment.